Discharge of Contract by Impossibility of the Fulfilment of Contractual Obligations Resulting from the Contract in a Non-Attributable Manner to the Obligor - Muhammad Abdolsaleh Shahnoosh Forushani (آموزه‌‌های فقه مدني)
The fulfilment of a contract may be made impossible by events involving the subject. The fulfilment of the contract may also not provide the primary purpose of its formation. This is sometimes attributable to the act or omission of one of the parties to the contract and sometimes it is not attributable to any of them. The verdict of impossibility (Arabic: تَعَذُّر) of the fulfilment of obligations arising from the contract in cases that cannot be attributed to one of its parties has been reviewed. Although sometimes “automatic cancellation in the case of destruction of the object of transaction before taking possession” and “nullity in case of impossibility of fulfillment of a contract” are considered to be the requirements of the exchange, it can be found another common aspect between the two rules and considered it as the reason for both rules and it should be considered as different expressions of the same rule. The invalidation in case of impossibility of fulfillment it and also the automatic cancellation of the contract in case of destruction of its subject matter before taking possession is the result of synallagmatic (bilateral) contract.